INTEGRASI NILAI-NILAI MODERASI BERAGAMA DI PONDOK PESANTREN NURUSSALAM DESA MENTAYAN KECAMATAN BANTAN KABUPATEN BENGKALIS - Sari, Elfi; Saputra, Hendi; Umam, Nurul (STAI Darul Qalam Tangerang, 2023)
The purpose of this study is to provide an explanation of the integration of religious moderation values at the Nurussalam Islamic Boarding School, Mentayan Village, Bantan District, Bengkalis Regency. This research is a qualitative research presented in the form of a description without intervention from the author. The results of the study reveal that in order to live life in a heterogeneous culture of society, it is necessary to strengthen the values of religious moderation, especially from within the pesantren itself. This is because Islamic boarding schools are used as the vanguard appointed by the community to restore universal Islamic teachings by taking the middle way (wasathiyah) by highlighting the values of religious moderation in order to create a harmonious life. In cultivating an attitude of religious moderation, Islamic boarding schools apply nine values that are included in various activities at the Nurussalam Islamic boarding school. The nine values in religious moderation are tawassuth (middle), I’tidal (perpendicular), tasamuh (tolerance), shura (deliberation), ishlah (reform), qudwah (pioneering), and muwathanah (love of the motherland), al -la'unf (non-violence) and I'tiraf al-'urf (culturally friendly).